The The Effectiveness of Progressive Muscle Relaxation in Reducing Anxiety and Sleep Disturbances in Hospitalized COVID-19 Patients: A Narrative Review - Muammar Ihsan; Luh Putu Miyako Mutiara Sari; Tabita Febyola Wijaya; Desi Mevlana Saputri (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Introduction: Coronavirus disease (COVID-19) has spread rapidly and massively from China to the rest of the world. Many of the hospitalized COVID-19 patients suffered from psychiatric symptoms such as anxiety and sleep disturbances, besides physical symptoms. Treatment of the psychiatric symptoms commonly used sedative, hypnotic, and anti-anxiety drugs. However, these drugs have some side effects. As an alternative, non-pharmacological intervention is needed. Some previous studies have shown that progressive muscle relaxation (PMR) can improve anxiety levels and sleep quality in other hospitalized patients. Therefore, this study was conducted to determine the effectiveness of PMR in hospitalized COVID-19 patients who experienced anxiety and sleep disturbances. Methods: We conducted a narrative review by searching for studies through PubMed and Google Scholar database with a publication time span from 2020 to 2021. Keywords used in the search: [“anxiety” or “sleep quality” or “sleep disturbances” or “COVID-19” or “patients”] and [“progressive muscle relaxation”]. Results: Based on the search result, we found three related articles: two randomized controlled trials and one observational study. The studies examined the effectiveness of PMR to improve anxiety and sleep quality in hospitalized COVID-19 patients. In the results of the three studies, PMR was effective in improving anxiety symptoms and sleep quality in COVID-19 patients. Conclusion: Considering not least of hospitalized COVID-19 patients who experienced anxiety and sleep disturbances, PMR as a non-pharmacological intervention can be implemented, because it is easy to perform and proven effective in reducing anxiety and sleep disturbances.